Entre caminhos e lugares do livro: gabinetes de leitura na região norte do Ceará (1877-1919) - Lima, Jorge Luiz Ferreira de (2011)
This work try to present the trajectory of the reading cabinets founded in the cities of Sobral Granja Ipu Camocim and Viçosa by newspapers books of memories and interviews It also tries to analyze the process of constitution of the collections of the reading cabinets of Ipu and Camocim whose whereabouts was possible to identify Starting from them we discuss the set up around the movement of the object book by the cities of the north area of Ceará retracing the paths taken from the production places and publication going by the bookstores located in main Centers distributors of the readers and the collections of the reading cabinets in the north region of Ceará In this effort we tried to demonstrate the existence of establishment connected with the sale of books in the area aiming to commercial firms as important points of distribution of didactic books liturgical manuals and devotional texts and more rarely literary works – novels The typographies are also seen as point of distribution and production of books in the region At the end we discussed the inclusion of the reading cabinets in the local memory.